Maximum Likelihood Performance of Mean Time to Failure for Right-Censored Data - Ibrahim, Noor Akma; Ng, Poh Bee (Institute for Mathematical Research, 2009)
In this paper failure times following Weibull, exponential and log-normal distribution are considered. The parameters of these distributions are estimated by the maximum likelihood method and these values are used to estimate other quantity of interest such as Mean Time to Failure (MTTF), an important function in a reliability analysis. This study is to look at the performance of maximum likelihood estimate (MLE) under various conditions by considering varying sample size and percentage of censored data. The performance is quantified from the study.